2001
DOI: 10.1111/j.1944-9720.2001.tb02064.x
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Reading Research on Passage Content and Gender: Challenges for the Intermediate‐Level Curriculum

Abstract: Second language (L2)reading research has shown that content schemata significantly influence comprehension. Howevel, a careful examination of available studies reveals disparities among research methods and procedures, thus making it difficult to formulate theories for re‐examining the intermediate‐level course, where the reading of lengthy, authentic texts begins. To complicate matters further, females begin to outnumber males at the intermediate level, and this gap widens at the advanced levels (Chavez, 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
2
21
0
2
Order By: Relevance
“…In most universities students in the advanced language courses enroll because they choose to, not because they are obliged to take the course in order to fulfill language requirements. Since we know very little about the advanced levels of language instruction in empirical terms, it is at this stage of acquisition where more L2 reading research is needed (Brantmeier, 2001;Young, 2003). At the advanced language levels of instruction, reading is often an individual act completed outside of the classroom, which underscores the importance of examining individual difference variables (IDVs) involved in the elusive process of L2 reading.…”
Section: Review Of the Literature Levels Of Second Language Instructionmentioning
confidence: 99%
“…In most universities students in the advanced language courses enroll because they choose to, not because they are obliged to take the course in order to fulfill language requirements. Since we know very little about the advanced levels of language instruction in empirical terms, it is at this stage of acquisition where more L2 reading research is needed (Brantmeier, 2001;Young, 2003). At the advanced language levels of instruction, reading is often an individual act completed outside of the classroom, which underscores the importance of examining individual difference variables (IDVs) involved in the elusive process of L2 reading.…”
Section: Review Of the Literature Levels Of Second Language Instructionmentioning
confidence: 99%
“…This, in turn, can have a major contribution to how they (males or females) approach the reading text and how they perform the reading questions. According to Brantmeier (2001), the content of a passage is related to one's achievement in reading. As he stated, men outperform on more science-oriented texts while women gain higher reading scores on subjects related to humanities.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a copious amount of studies have demonstrated that learning tendencies and behavior are reflected in different manners by gender (Tsai & Tsai, ). For instance, Brantmeier () found that gender was a key concern associated with reading comprehension in a group of readers whose reading language was their second language. Moreover, Pae () investigated the effect of gender on EFL reading comprehension, and the results showed that females were in favor of mood/impression/tone items, whereas males preferred logical inference items.…”
Section: Literature Reviewmentioning
confidence: 99%